The Value Of Property Companies: Role Of Profitability, Leverage, And Liquidity - Agistia, Irine; Santoso, Fahrul Imam (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study aims to analyze the effect of profitability, leverage and liquidity on the value of property companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The population was 84 property and real estate companies listed on the Indonesia Stock Exchange. The sample obtained using purposive sampling was 12 companies with 5 years of data, resulting in a total of 60 sample data. All data analyses are conducted using statistical software such as SPSS. The results of the study show that each variable of profitability, leverage, and liquidity has a positive effect on company value. Profitability as measured by the net profit ratio, is proven to be the main factor that increases company value, reflecting the company's ability to generate sustainable profits. Leverage measured by the debt to equity ratio also shows a positive effect, indicating that wise use of debt can increase company value. Meanwhile, liquidity, measured by the current ratio, shows that companies with good liquidity are better able to meet short-term obligations, thereby increasing investor confidence. This study provides important insights for property company management in formulating effective financial strategies to increase company value. These findings also suggest the need for more attention to the management of these three variables to achieve sustainable growth in the property market.